A Study on Guest-Host Liquid Crystal Polarizer Technology to Improve the Transmittance of Polarized Closed-Circuit Television - Lee, Na-Kyung; Ahn, Hyeon-Sik; Choi, Yoonseuk (International Conference on Electronics, Information and Communications (Online), 2024)
In this study, we propose a system that can switch between polarized closed-circuit television(CCTV) and general CCTV by applying dichroic dye-doped liquid crystal-based polarizer technology to CCTV. The polarizing film attached to existing polarizing CCTV generally reduces the amount of light transmittance by 50%, which limits the use of CCTV at night and in dark places. Therefore, when using existing polarizing CCTV in a dark environment, the polarizing film must be physically removed and attached. However, by using guest-host liquid crystal (GHLC), polarization mode and general CCTV mode can be electrically adjusted when there is little light reflected on the subject. Additionally, the transmittance can be adjusted depending on the intensity of the voltage, allowing optimization to suit the situation. Polarization images obtained by applying this technology can be derived into optimal images using computer software. Through the development of this technology, it is expected that the liquid crystal polarizer, which can electrically switch between polarization mode and transmission mode, will be applied to polarized CCTV and be applied in various environments.